2023
DOI: 10.14202/vetworld.2023.638-649
|View full text |Cite
|
Sign up to set email alerts
|

The role of probiotics in vannamei shrimp aquaculture performance – A review

Abstract: Vannamei shrimp (Litopenaeus vannamei) is an important food commodity of economic benefit due to its high price, low susceptibility to disease, and popularity for consumption. These advantages have led many farmers to cultivate vannamei shrimp. Efforts are underway to improve the aquaculture performance of this species, including the use of probiotics, which are non-pathogenic bacteria that aid in digestion and help fight disease. Probiotics are usually obtained from the intestines of vannamei shrimp or the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Nevertheless, the highest weight gain was achieved in probiotic only treated (treatment A) implying that probiotic could provide it maximal effect on healthy shrimp compared to infected shrimp. In several studies using other bacterial species, probiotics has been shown to bring a lot of benefit to the growth of L. vannamei (Amiin et al, 2023). One reason is that probiotics could aid in food digestion via breaking down complex into simpler molecules such that it can be easily absorbed in the intestine.…”
Section: Effect Of Probiotics On Shrimp Body Weight and Length Gainsmentioning
confidence: 99%
“…Nevertheless, the highest weight gain was achieved in probiotic only treated (treatment A) implying that probiotic could provide it maximal effect on healthy shrimp compared to infected shrimp. In several studies using other bacterial species, probiotics has been shown to bring a lot of benefit to the growth of L. vannamei (Amiin et al, 2023). One reason is that probiotics could aid in food digestion via breaking down complex into simpler molecules such that it can be easily absorbed in the intestine.…”
Section: Effect Of Probiotics On Shrimp Body Weight and Length Gainsmentioning
confidence: 99%
“…Langkah pengelolaan lingkungan yang bisa dilakukan yakni pengenceraan untuk menaikkan kecerahan, penambahan dosis molase untuk menaikkan populasi plankton serta mengurangi populasi bakteri patogen. Menurut Amiin et al, (2023) aplikasi probiotik pada budidaya udang bermanfaat unuk menjaga kualitas air.…”
Section: Aspek Sosiologiunclassified
“…Probiotic delivery methods are diverse and often depend on the type of facility, age, and species of fish [62]. Currently, the methods of administration in aquaculture are injection or addition to the water column or feed [24,63]. Certain factors must be taken into account before choosing the route of administration.…”
Section: Technological Aspects and Administration Routes Of Probioticsmentioning
confidence: 99%